Women and Rural Sufism Movements: Portrait of the Female Yassin Pilgrims “Al-Hidayah” Bangunrejo Kidul Village - Mibtadin Mibtadin (Javanologi: International Journal of Javanese Studies, 2023)
Religious traditions in rural areas, one of which is yassinan became a medium for women's religious expression through spiritual groups such as the female yassin pilgrims “Al-Hidayah.” How yassin putri “AlHidayah” of Bangunrejo Kidul community in developing personal spirituality and humanity. Descriptive qualitative research methods, using a sociology of religion approach, and data analysis through interactive analysis models include data reduction, data submission, and drawing conclusions. The yassinan tradition is a tradition that has been passed down for generations in the community of Bangunrejo Kidul Kedunggalar Ngawi Village. This tradition has the benefit of two values, namely: first, the religious value in the form of habl min Allah as a religious expression to train and accustom the pilgrims of yassin putri and the community to read kalimah ţayyibah, dhikr, prayer, shalawat, and chant quranic verses intended to get ridho Allah Swt. This tradition is carried out every Thursday in addition to praying for the dead, it also provides spiritual comfort, tranquility, coolness of heart, and increased faith of the community. Second, social values in the form of habl min nas strengthen social ties, strengthen the ropes of silaturrahmi, ngraketake taline kekadangan to realize ukhuwah Islamiyah, ukhuwah wathoniyah, and ukhuwah insaniyah. The existence of an emotional bond of "yassin pilgrims " is able to foster a sense of brotherhood, social interaction, and unity of Muslims in the community of Bangunrejo Kidul Village.Keywords : Rural Sufism, the Female Yassin Pilgrims, Al-Hidayah, Social Piety